Development and evaluation of a framework for global flood hazard mapping. (August 2016) - Dottori, Francesco; Salamon, Peter; Bianchi, Alessandra; Alfieri, Lorenzo; Hirpa, Feyera Aga; Feyen, Luc
Highlights: We derive global flood hazard maps at 30′′ resolution for several return periods The mapping procedure is based on a hydrological and hydraulic modelling chain Maps are evaluated using official and satellite-derived flood extent maps Abstract: Nowadays, the development of high-resolution flood hazard models have become feasible at continental and global scale, and their application in developing countries and data-scarce regions can be extremely helpful to increase preparedness of population and reduce catastrophic impacts. The present work describes the development of a novel procedure for global flood hazard mapping, based on the most recent advances in large scale flood modelling. We derive a long-term dataset of daily river discharges from the hydrological simulations of the Global Flood Awareness System (GloFAS). Streamflow data is downscaled on a high resolution river network and processed to provide the input for local flood inundation simulations, performed with a two-dimensional hydrodynamic model. All flood-prone areas identified along the river network are then merged to create continental flood hazard maps for different return periods at 30′′ resolution. We evaluate the performance of our methodology in several river basins across the globe by comparing simulated flood maps with both official hazard maps and a mosaic of flooded areas detected from satellite images. The evaluation procedure also includes comparisons with the results of other large scale flood models. We further investigate the sensitivity of the flood modelling framework to several parameters and modelling approaches and identify strengths, limitations and possible improvements of the methodology.